2006
DOI: 10.7150/ijbs.2.23
|View full text |Cite
|
Sign up to set email alerts
|

Seminal malondialdehyde concentration but not glutathione peroxidase activity is negatively correlated with seminal concentration and motility

Abstract: Objectives: Reactive oxygen species (ROS) induced lipid peroxidation is associated with sperm function. Malondialdehyde (MDA) concentration and glutathione peroxidase (GPx) activity represent the lipid peroxidation and spermicidal antioxidant, respectively. We aimed to evaluate the relationship of MDA and GPx levels with sperm parameters.Patients and methods: Specimens were divided into two groups: group 1. normospermia (n=20); group 2. oligoasthenospermia (n=31). Seminal MDA concentration was measured by thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
79
3
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 39 publications
13
79
3
5
Order By: Relevance
“…Suleiman et al (1996) demonstrated that the MDA concentration in the seminal plasma was not correlated with the sperm concentration and motility. In this work the negative significant correlation was observed between lipid peroxidation with sperm concentration, motility and normal morphology between fertile and infertile men which was compatible with the findings of Kobayashi et al (1991), Huang et al (2000), Hsieh et al (2006), Zalata et al (2004), Suleiman et al (1996) and Gomez et al (1998). But this correlation was not significant in the fertile or infertile men.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Suleiman et al (1996) demonstrated that the MDA concentration in the seminal plasma was not correlated with the sperm concentration and motility. In this work the negative significant correlation was observed between lipid peroxidation with sperm concentration, motility and normal morphology between fertile and infertile men which was compatible with the findings of Kobayashi et al (1991), Huang et al (2000), Hsieh et al (2006), Zalata et al (2004), Suleiman et al (1996) and Gomez et al (1998). But this correlation was not significant in the fertile or infertile men.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, this decrease in fluidity could affect the membrane transport activity and thereby affect on the surviving of sperm. A number of studies have shown that lipid peroxidation affects the sperm concentration, motility, morphology and related with poor sperm quality (Huang et al 2000;Hsieh et al, 2006;Gomez et al, 1998). Kobayashi et al (1991) demonstrated that MDA level in spermatozoa was significantly related to the number of immotile sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm membrane lipid peroxidation status, measured by malondialdehyde (MDA) concentration, is the main nonconventional measurable marker of oxidative stress in semen. Malondialdehyde levels have often been correlated with deterioration of sperm quality [82][83][84]. An association between the presence of some known pathogens, such as U. urealyticum or C. trachomatis, and the induction of sperm lipid peroxidation, as judged by the MDA levels, has also been suggested [17,26].…”
Section: Role Of Oxidative Stressmentioning
confidence: 99%
“…Samples showing more than 60% of swollen spermatozoa were classified as HOS positive and those with less than 60% as HOS negative 6 . Estimation of seminal plasma malondialdehyde (MDA) concentration: Seminal MDA concentration was measured by thiobarbituric acid reaction method 7 . …”
Section: Methodsmentioning
confidence: 99%